PARTISIPASI MASYARAKAT DALAM PROGRAM GERAKAN SERENTAK MEMBANGUN KAMPUNG (GSMK) DI KECAMATAN GEDUNG AJI BARU KABUPATEN TULANG BAWANG - Rahmad Hidayat Batubara; Irwan Effendi; Rio Tedi Prayitno (Lampung University, 2016)
The purposes of this research are to analize about 1) The level of people’s participation in Gedung Aji Baru District, Tulang Bawang Regency on GSMK’s Program, 2) People’s group role on powering people’s participation on GSMK’s Program in Gedung Aji Baru District, Tulang Bawang Regency, 3) The relationship between people group role and people participation’s level on GSMK’s Program at Gedung Aji Baru District, Tulang Bawang Regency. This study was conducted in Gedung Aji Baru District, Tulang Bawang Regency. The number of samples on this research were 98 respondents choosen by Proportional Random Sampling method, and the method of analysis used Rank Spearman correlation. The results showed 1) Most of society have already participated very well on GSMK’s program in Gedung Aji Baru subdistrict of Tulang Bawang regency, although there are society of Village Sido Mekar who haven’t well participated yet. 2) Most of people’s group role moved the society participation in Gedung Aji Baru subdistrict of Tulang Bawang regency was acted very well, although there are people’s group role act activeless whitin identified self-supporting potential and people’s participation are people’s group role of Sido Mekar village. 3) The research result show that people’s group role as high as level of society participation. Key words: GSMK’s Program, participation, people’s group, public